The drift response to the applied electric field in an InGaAs quantum-well nanostructure - Chii, Aaron Enn Lee (2007)
InGaAs, or indium gallium arsenide, is an alloy of gallium arsenide and indium arsenide. In a more general sense, it belongs to the InGaAsP quaternary system that consists of alloys of indium arsenide (InAs), gallium arsenide (GaAs), indium phosphide (InP), and gallium phosphide (GaP). As gallium and indium belong to Group III of the Periodic Table, and arsenic and phosphorous belong to Group V, these binary materials and their alloys are all III-V compound semiconductors.